Fractional-order filter design for set-point weighted PID controlled unstable systems - Bingi, K. (International Journals of Engineering and Sciences Publisher, 2017)
Control of unstable systems with conventional PID controllers gives poor set-point tracking and disturbance rejection performance. The use of set-point weighted PID controllers (SWPID) to improve the control performance with respect to set-point tracking and disturbance rejection have been attempted. This is due to the fact that, SWPID will reduce proportional and derivative kicks in the control action. However, the control signal of SWPID controller is still inheriting the PID's undesired oscillations in the control signal. This leads to faster degradation of actuators. In this work, a fractional-order lowpass filter is designed alongside SWPID controller for unstable systems. Incorporating such filter will help to reduce undesired oscillations. The result's comparison shows that the performance of SWPID with fractional-order filter is better compared to its performance with an integer-order filter. This is true for all the three unstable systems considered. © October 2017 IJENS.